Trends in the Use of Infographic Media in Learning Islamic Religious Education - Syahrul Prayoga, Andry; Mustaghfirah, Walidatul; Fatimatur Rusydiyah, Evi (Jurnal Pendidikan Islam Indonesia, 2024)
This study aims to examine the trend of using infographic media in learning Islamic religious education. The use of technology-based media, especially infographics, was rarely applied in Islamic education learning. Teachers used infographic learning media but the frequency was low. The infographics used were generally only found in the Learner Worksheets or learning package books with teaching methods that still dominantly use books, blackboards and discussions. The research method used a qualitative approach with a case study research type. The subjects were PAI teachers, students, and school principals. The data collection techniques used included observation, interviews, and documentation. Data analysis was conducted using qualitative data analysis techniques that follow Yin's concept, which includes pattern matching, building clarity, time series analysis, logic models, and cross-cases. The results showed that PAI teachers actively integrate infographic media in the learning process to current learning media trends. The use of infographic media proved to improve students' understanding of Islamic concepts, enrich the learning experience, and facilitate the delivery of complex information more interestingly and understandably. infographics also increase students' engagement in learning and motivate them. Evaluation of the use of infographics showed significant improvements in students' understanding of memory and interest. This study concludes that the use of infographic media was effective in improving, motivating and increasing students' involvement.